2017
DOI: 10.9778/cmajo.20160102
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use during pregnancy: a population-based cohort study

Abstract: Background:Opioid use has increased dramatically in North America. The safety of opioids in pregnancy is uncertain, but they are associated with several fetal abnormalities and contribute to rising rates of neonatal abstinence syndrome. We examined opioid use before and during pregnancy in a complete population-based cohort. Methods:We examined opioid use in a cohort of all pregnant women in Manitoba, Canada, from 2001 to 2013. Opioid use was defined by prescriptions for opioids, converted to oral morphine equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
3
16
1
Order By: Relevance
“…Our prevalence estimate of opioid use during pregnancy (1.4%) is lower than the prevalence estimates by Falk et al [17] based on the percentage of women filling opioid prescriptions before and during pregnancy among a cohort of pregnant women in Manitoba. Falk et al [17] found that while almost 7% filled prescriptions for opioids in the 3 months before pregnancy, this declined to 4.2%, 3.0% and 2.9% in the first to third trimesters, respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…Our prevalence estimate of opioid use during pregnancy (1.4%) is lower than the prevalence estimates by Falk et al [17] based on the percentage of women filling opioid prescriptions before and during pregnancy among a cohort of pregnant women in Manitoba. Falk et al [17] found that while almost 7% filled prescriptions for opioids in the 3 months before pregnancy, this declined to 4.2%, 3.0% and 2.9% in the first to third trimesters, respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…No differences were observed in the number of the purchases of opioids Previous studies, including both primiparous and multiparous women, have shown a wide range in the prevalence of opioid use during pregnancy; varying from 22% in southern parts of the United States to 6% in Norway and 5% in Sweden. 7,[9][10][11]14 Our study finding that 5% of primiparous Finnish women used opioid drugs during pregnancy is consistent with previous Scandinavian studies. 7,11 When focusing upon the time periods of the purchases of opioids, the study findings have been inconsistent.…”
Section: Discussionsupporting
confidence: 92%
“…However, no reduction was reported when morphine equivalent units were used to measure the use of opioids. 10 A Norwegian study reported less opioids purchases as pregnancy progressed, 11 while Swedish and US studies reported the opposite. 4,7,9 Codeine was the most commonly used opioid among pregnant Finnish primiparous women; 96% of women who used opioids used codeine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations